Effects of Zinc-Free Processing Aids on Silica-Reinforced Tread Compounds for Green Tires - Nam Chul Kim; Sung Ho Song (International Journal of Polymer Science)
With the development of “green tires” in the tire industry, the conventional carbon black filler that is used in tread formulations is being replaced with silica. Generally, this requires the addition of a processing aid, containing zinc ion, which acts as a lubricant and dispersing agent. However, because zinc is a heavy metal, zinc-free processing aids (ZFAs) are required to satisfy worldwide environmental concerns. We present herein a series of catalytically synthesized ZFAs and evaluate the effects of replacing zinc ion-containing processing aids (ZCAs) on a silica tread formulation. Interestingly, replacing ZCA with ZFA in a two parts per hundred rubber (phr) by weight formulation improved both its tensile strength and elongation by as much as 31% and 20%, respectively. ZFA-rubber formulations also exhibited a twofold enhancement in fatigue properties over those of ZCA-rubber formulations. Furthermore, pneumatic tires were fabricated from our ZFA-rubber formulation and compared against tires containing ZCAs. The ZFA-rubber composite exhibited improved dry and wet braking and rolling resistance due to enhanced dispersion of silica in the rubber matrix. These results show that rubber composites prepared with ZFAs may be promising in tire engineering applications.